Report of the working Group on Assessment of Pandalus Stocks ... - ICES (ICES Expert Group reports (until 2018), 2023)
The Working Group on the Assessment of Pandalus Stocks (Chairman: Mr S. Munch-Petersen) met at ICES Headquarters from 12-16 February 1990 (C.Res.1989/2:4:1) to:1) assess the status of the stocks of Pandalus borealis in the North Sea, Skagerrak, and Kattegat,2) evaluate the basis for treating Pandalus in the Norwegian Deeps and Division IlIa as separate stock units and, if appropriate, make an assessment for these units combined. ...